The characteristics and alteration of peripheral immune function in patients with multiple system atrophy - Wang, Minghui; Yan, Zhaofen; Wang, Jing; Yang, Yujiao; Deng, Qinqin; Han, Yixian; Zhang, Liping; Yang, Huajun; Pan, Jiali; Wang, Mengyang (Frontiers in Neurology, 2023)
Objective: Multiple system atrophy (MSA) is a degenerative disease. The immune dysfunction acted a crucial role in the pathogenesis of this disease in previous literatures, while the characteristics of peripheral immune function was unclear. This study aimed to investigate the characteristics and alterations of peripheral immune function in patients with MSA. Methods: A case-control study was conducted between January 2021 to December 2022 at SanBo Brain hospital, Capital Medical University, Beijing, China. A total of 74 participants were recruited, including 47 MSA patients and 27 non-MSA participants. Peripheral blood samples were collected from each participant. 29 types of immune cells were measured using flow cytometry analysis technology. Single factor analysis and multiple factor analysis (multiple linear regression models) were performed to determine the differences and risk factors in immune cells between the MSA and non-MSA groups. Results: Alterations of the count or percentage of CD19+ B lymphocyte, and CD3-CD56+ B lymphocyte in MSA patients were found in this study. The reductions of the count and percentage of CD19+ B lymphocyte were still robust after adjusting for variables of age, gender, body mass index, albumin, and hemoglobin. Furthermore, the reductions in the count and percentage of CD19+ B lymphocyte in the MSA patients were more significant in women and individuals aged 60 years old or above than the non-MSA participants. Conclusion: Our findings suggested that the MSA patients may influenced B lymphocytes, particularly CD19+ cells. Therefore, the reductions in immune cells should be considered in the diagnosis and treatment of MSA. Further studies are warranted to confirm and expand upon these findings.